The Missionary Diary as a Spiritual Autobiography (Based on the Diaries of Saint Nicholas of Japan) - Natalia V. Kartasheva (Вестник Свято-Филаретовского института)
The article emphasizes the significance of a personalized approach in the investigation of the history of Russian Orthodox missionary work. Personal sources, such as diaries and letters, serve as the most comprehensive and trustworthy materials for biographical research. The methodology for studying these sources is actively evolving in the field of humanities. The traditional approach, which views personal documents as a source of historical information, is contrasted with the narrative approach, where the diary is seen as a narrative in which the author “speaks for themselves”, revealing their multifaceted personality. The missionary diary is characterized by its thematic focus, as it not only provides a formal account of missionary activities but also offers insights into the missionary’s inner thoughts and reflections. Additionally, the missionary diary shares similarities with travel literature. At the same time, the diary reflects the missionary’s complex perspective on the space of his ministry, which is both foreign and familiar. The legacy of St. Nicholas of Japan allows to see the diary of the missionary as a unique form of spiritual biography. Its most characteristic feature is that the text does not appear to be a linear narrative; rather, it is a collection of individual experiences recorded in the diary. This process of narrativization not only captures personal experiences but also helps to understand, comprehend, and contextualize them within the cultural framework of one’s life. The analysis of diary entries revealed such aspects of the saint’s personality as intense emotions, broad-mindedness, sincerity, confession, constant prayerful work, and unwavering commitment to the goal. The approaches presented in the article for the analysis of missionary diaries can be a starting point for expanding the scope of research in the field of Russian Orthodox mission. The examination of missionary reflections in the diaries of prominent figures of the Russian Orthodox mission in the past is of great significance for the advancement of both theoretical and practical aspects of contemporary mission.